A high-content solid waste-based zero-cement addition non-fired and non-steamed brick and a preparation method thereof
By using solid waste such as fly ash, calcium carbide slag and gypsum, combined with nano-microsilicon powder and retarder, and using a small amount of water glass to excite, the existing fire-free and steam-free brick process is solved and the problem of alkali-returning bricks with high compressive strength and durability is achieved.
Patent Information
- Application Number
- CN202310223876.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-09
AI Technical Summary
The existing fire-free and steam-free brick process is complicated, and the large amount of alkali exciter is used to cause alkali return. It is difficult to balance the amount of solid waste and cement, and the strength and durability are insufficient.
Solid waste such as fly ash, calcium carbide slag and gypsum are used as raw materials, nano-silicon powder, mineral powder and retarder are added, and a small amount of water glass is used as alkaline exciter to form a dense gel phase to improve the strength and durability of the brick.
It achieves high compressive strength without pressurization molding. The compressive strength can reach 34MPa in 14 days of maintenance and 40MPa in 28 days of compression. There is no obvious alkali reflux on the surface of the brick. The process is simple and the maintenance cost is reduced.
Smart Images

Figure CN116253541B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a high-content solid waste-based zero-cement addition non-fired and non-steamed brick and a preparation method thereof. Background Art
[0002] Brick building materials are an ideal application direction for solid waste resource utilization, which can greatly reduce the use of natural resources. Unsteamed and unfired bricks are a new type of brick building material that uses construction waste and industrial solid waste as the main powder raw materials, cement, water reducer additives, etc. as auxiliary materials, and is manufactured without high-temperature calcination. This type of building material has the advantage of a wide range of raw material sources and is a green and environmentally friendly building material. However, there are currently common problems such as complex processes, large amounts of alkali activators causing alkali reversion, balance between solid waste and cement, and strength and durability issues.
[0003] Chinese patent CN113929371A discloses a method for preparing all-solid waste unburned bricks using solid waste from multiple industries. Under the conditions of pressure molding and steam curing, the compressive strength can reach 20-28MPa after 28 days of curing.
[0004] Chinese patents CN112408935A, CN111892364A, CN113307576 A, etc. all disclose methods for preparing unfired and unsteamed bricks based on solid waste, but all of them require the use of commercial cement to form a cementitious system to improve the strength of the brick body.
[0005] Chinese patent CN114031341A discloses a method for preparing fire-free and steam-free solidified bricks based on solid waste. The process flow is relatively complicated and requires pressure molding to reach above 25MPa. In addition, carbon curing is required to alleviate the alkali return problem. Summary of the invention
[0006] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a high-solid waste-based zero-cement-added fire-free and steam-free brick and a preparation method thereof. Fly ash, carbide slag, gypsum and other solid wastes are used as raw materials, nano-silicon powder, mineral powder and retarder are used as additives, and a small amount of water glass is used as an alkali activator to stimulate the activity of fly ash and other raw materials, form a dense gel phase, and improve the strength and durability of the brick body. The fire-free and steam-free bricks provided by the present invention can reach a compressive strength of 34Mpa after 14 days of curing and a compressive strength of 40MPa after 28 days of curing by adjusting the content of nano-silicon powder without the need for a pressure molding process, and there is no obvious alkali reversion phenomenon on the surface of the brick body.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A high-content solid waste-based zero-cement addition non-burning and non-steaming brick, comprising the following raw materials in parts by weight:
[0009] 65-75 parts of fly ash, 5-10 parts of carbide slag, 10-15 parts of gypsum, 10-20 parts of nanosilica powder, 10-20 parts of mineral powder, 5-10 parts of water glass, 0.1-0.2 parts of retarder, and 50-55 parts of water;
[0010] The retarder is a five-element copolymer with methylthioallyl alcohol polyoxyethylene ether (molecular formula: (C2H4O)nC4H8SO, number average molecular weight: 3800) as a functional monomer;
[0011] The five-element copolymer is polymerized by methylthioallyl alcohol polyoxyethylene ether, acrylic acid, butyl acrylate, mercaptopropionic acid, and vitamin C; the retarder is a five-element copolymer of methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C; the number average molecular weight of the five-element copolymer is 40000-44000. The low dosage of the five-element copolymer can improve the strength of the material, and the high dosage can achieve a retarding effect, but the strength will be lost.
[0012] The size of the nano-silicon powder is 20-200nm, the SiO2 content is higher than 90%, and the specific surface area is 25-30m 2 / g.
[0013] The preparation method of the five-membered copolymer is as follows:
[0014] 180 parts by weight of methylthioallyl alcohol polyoxyethylene ether are added to 1000 parts by weight of deionized water, heated to dissolve, 2.5 parts by weight of hydrogen peroxide are added, and then 50 parts by weight of a deionized water solution containing 20 parts by weight of acrylic acid, 20 parts by weight of butyl acrylate, 1.2 parts by weight of mercaptopropionic acid and 0.5 parts by weight of vitamin C are dripped at a uniform rate, and sodium bicarbonate solution is added to adjust the pH to 6.5, and the reaction temperature is controlled to maintain at 80°C for 8 hours to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer.
[0015] A method for preparing high-content solid waste-based zero-cement addition non-fired and non-steamed bricks, comprising the following steps:
[0016] S1: fly ash, carbide slag, gypsum and mineral powder are mixed in proportion to obtain a premixed dry powder;
[0017] S2: Mix and stir nanosilica powder, water glass and half of water in proportion to obtain an excitation enhancer;
[0018] S3: adding the excitation enhancer and the retarder to the premixed dry powder, and adding the remaining half of the water, stirring to obtain a gelling material;
[0019] S4: putting the mixed cementitious material into a mold and vibrating it to obtain a green brick;
[0020] S5: placing the green bricks at a temperature of 20-30° C. and a humidity of 95-99% for curing for 14-28 days to obtain the unfired and unsteamed bricks.
[0021] Beneficial effects of the present invention:
[0022] (1) The present invention selects solid wastes such as fly ash, carbide slag, gypsum, etc. as raw materials, and the solid waste utilization rate is as high as more than 70%. A large amount of solid waste can be consumed, thereby realizing the greening of the building materials industry and effectively alleviating the problem of natural resources.
[0023] (2) The present invention has simple steps and does not require the introduction of commercial cement as a gel material. Nanosilica powder can be used as a pre-dispersed carrier to form a crystal nucleus phase to significantly improve mechanical properties and durability. By introducing a five-membered copolymer of methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C as a retarder and adjusting the amount of nanosilica powder added, the compressive strength of commercial bricks can reach 20-40MPa after curing for 14-28 days, which can meet different construction needs and effectively reduce the maintenance cost.
[0024] (3) Due to the small amount of water glass used, commercial bricks have no obvious alkali reversion phenomenon and are highly practical.
[0025] (4) In the process flow, there is no need for pressure forming, and the compressive strength can reach that of ordinary pressure-formed, non-fired, non-steamed curing bricks. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0027] Figure 1 It is a scanning electron microscope photograph of the nano-silicon powder used in the present invention.
[0028] Figure 2 This is a physical photograph of the alkali reversion test of the finished product of the unfired and steamed brick prepared in Example 1 of the present invention.
[0029] Figure 3 This is a physical photograph of the alkali reversion test of the unfired and steamed brick product prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited to these embodiments.
[0031] The fly ash used in the examples and comparative examples is the raw ash from the power plant in Ningxia Autonomous Region. Its main components are silicon dioxide, aluminum oxide, iron oxide, calcium oxide, magnesium oxide, etc. The particle size distribution is uneven, mainly concentrated in 0.5-40 microns. The size of nanosilicon powder is 20-200nm, the SiO2 content is higher than 90%, and the specific surface area is 25-30m 2 / g. The main components of carbide slag are calcium oxide (65.9wt%), silicon dioxide (8.4wt%), magnesium oxide (1.5wt%) and a small amount of aluminum oxide and iron oxide, with a specific gravity of 1.82. Gypsum mainly becomes calcium sulfate dihydrate (99wt%). The main components of mineral powder are silicon dioxide (31.9wt%), calcium oxide (36.2wt%), aluminum oxide (17.2wt%) and magnesium oxide (10.5wt%).
[0032] Preparation of methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer:
[0033] 180 g of methylthioallyl alcohol polyoxyethylene ether (number average molecular weight of 3800) was added to 1000 ml of deionized water, stirred and dissolved at 50°C, 2.5 g of hydrogen peroxide was added, and then 50 ml of a deionized water solution containing 20 g of acrylic acid, 20 g of butyl acrylate, 1.2 g of mercaptopropionic acid and 0.5 g of vitamin C was uniformly dropped into the above solution (dropping time 10 min), and sodium bicarbonate solution (0.1 mol / L) was added to adjust the pH to 6.5, and the reaction temperature was controlled to maintain at 80°C for 8 h to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer (retarder A) with a number average molecular weight of 42000.
[0034] 170 g of methylthioallyl alcohol polyoxyethylene ether (number average molecular weight of 3800) was added to 1000 ml of deionized water, stirred and dissolved at 50°C, 2.5 g of hydrogen peroxide was added, and then 50 ml of a deionized water solution containing 18 g of acrylic acid, 20 g of butyl acrylate, 1.2 g of mercaptopropionic acid and 0.5 g of vitamin C was uniformly dropped into the above solution (dropping time 10 min), and sodium bicarbonate solution (0.1 mol / L) was added to adjust the pH to 6.5, and the reaction temperature was controlled to maintain at 80°C for 6 h to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer (retarder B) with a number average molecular weight of 40,000.
[0035] 190 g of methylthioallyl alcohol polyoxyethylene ether (number average molecular weight of 3800) was added to 1000 ml of deionized water, stirred and dissolved at 50°C, 2.5 g of hydrogen peroxide was added, and then 50 ml of a deionized water solution containing 22 g of acrylic acid, 20 g of butyl acrylate, 1.2 g of mercaptopropionic acid and 0.5 g of vitamin C was uniformly dropped into the above solution (dropping time 10 min), and sodium bicarbonate solution (0.1 mol / L) was added to adjust the pH to 6.5, and the reaction temperature was controlled to maintain at 80°C for 9 h to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer (retarder C) with a number average molecular weight of 44000.
[0036] 160 g of methylthioallyl alcohol polyoxyethylene ether (number average molecular weight of 3800) was added to 1000 ml of deionized water, stirred and dissolved at 50°C, 2.5 g of hydrogen peroxide was added, and then 50 ml of a deionized water solution containing 18 g of acrylic acid, 18 g of butyl acrylate, 1.2 g of mercaptopropionic acid and 0.5 g of vitamin C was uniformly dropped into the above solution (dropping time 10 min), and sodium bicarbonate solution (0.1 mol / L) was added to adjust the pH to 6.5, and the reaction temperature was controlled to maintain at 80°C for 6 h to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer (retarder E) with a number average molecular weight of 38000.
[0037] 195 g of methylthioallyl alcohol polyoxyethylene ether (number average molecular weight of 3800) was added to 1000 ml of deionized water, stirred and dissolved at 50°C, 2.5 g of hydrogen peroxide was added, and then 50 ml of a deionized water solution containing 22 g of acrylic acid, 22 g of butyl acrylate, 1.2 g of mercaptopropionic acid and 0.5 g of vitamin C was uniformly dropped into the above solution (dropping time 10 min), and sodium bicarbonate solution (0.1 mol / L) was added to adjust the pH to 6.5, and the reaction temperature was controlled to maintain at 80°C for 8 h to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer (retarder F) with a number average molecular weight of 46000.
[0038] Preparation of methyl allyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer:
[0039] 180 g of methyl allyl alcohol polyoxyethylene ether was added to 1000 ml of deionized water, stirred and dissolved at 50°C, 2.5 g of hydrogen peroxide was added, and then 50 ml of a deionized water solution containing 20 g of acrylic acid, 20 g of butyl acrylate, 1.2 g of mercaptopropionic acid and 0.5 g of vitamin C was uniformly dropped into the above solution (dropping time 10 min), and sodium bicarbonate solution (0.1 mol / L) was added to adjust the pH to 6.5, and the reaction temperature was controlled to maintain at 80°C for 8 h to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer (retarder A) with a number average molecular weight of 41000.
[0040] Example 1
[0041] S1: Add 70kg fly ash, 7.5kg carbide slag, 12.5kg gypsum and 17.5kg mineral powder into a mixing kettle, stir at 600 rpm for 5 minutes to mix well, and obtain a premixed dry powder;
[0042] S2: Add 20 kg of nano-silica powder, 10 kg of water glass and 25 kg of water into another mixing kettle and stir and mix well to obtain an excitation enhancer;
[0043] S3: Add the excitation enhancer and 0.2 kg of retarder A (methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-member copolymer) to the premixed dry powder, add 25 kg of water, stir (stir at 600 rpm for 5 minutes), mix well, and obtain a gelling material;
[0044] S4: putting the mixed cementitious material into a mold and vibrating it to obtain a green brick;
[0045] S5: placing the green bricks at a temperature of 25° C. and a humidity of 95% for curing for 28 days to obtain unfired and unsteamed bricks.
[0046] Example 2
[0047] S1: Add 65kg fly ash, 5kg carbide slag, 10kg gypsum and 10kg mineral powder into a mixing kettle and stir at 600 rpm for 5 minutes to obtain a premixed dry powder;
[0048] S2: Add 15 kg of nano-silica powder, 5 kg of water glass and 25 kg of water into another mixing kettle, stir and mix well to obtain an excitation enhancer;
[0049] S3: Add the excitation enhancer and 0.1 kg of retarder B (methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-element copolymer) to the premixed dry powder, add 25 kg of water, stir (stir at 600 rpm for 5 minutes), mix well, and obtain a gelling material;
[0050] S4: putting the mixed cementitious material into a mold and vibrating it to obtain a green brick;
[0051] S5: placing the green bricks at a temperature of 20° C. and a humidity of 97% for curing for 28 days to obtain unfired and unsteamed bricks.
[0052] Example 3
[0053] S1: Add 75kg fly ash, 10kg carbide slag, 15kg gypsum and 20kg mineral powder into a mixing kettle, stir at 600 rpm for 5 minutes to mix well, and obtain a premixed dry powder;
[0054] S2: Add 20 kg of nano-silica powder, 10 kg of water glass and 27.5 kg of water into another mixing kettle and stir and mix well to obtain an excitation enhancer;
[0055] S3: Add the excitation enhancer and 0.2 kg of retarder C (methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-member copolymer) to the premixed dry powder, add 27.5 kg of water, stir (stir at 600 rpm for 5 minutes), mix well, and obtain a gelling material;
[0056] S4: putting the mixed cementitious material into a mold and vibrating it to obtain a green brick;
[0057] S5: placing the green bricks at a temperature of 30° C. and a humidity of 99% for curing for 28 days to obtain unfired and unsteamed brick products.
[0058] Example 4
[0059] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the amount of nanosilica powder added in step S2 is 15 kg.
[0060] Example 5
[0061] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the amount of nanosilica powder added in step S2 is 10 kg.
[0062] Example 6
[0063] The preparation method of the unfired and unsteamed brick product is basically the same as the preparation method of Example 1, except that the amount of water glass added in step S2 is 5 kg.
[0064] Comparative Example 1
[0065] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the amount of nanosilica powder added in step S2 is 5 kg.
[0066] Comparative Example 2
[0067] The preparation method of the unfired and unsteamed brick product is basically the same as the preparation method of Example 1, except that nanosilicon powder is not added in step S2.
[0068] Comparative Example 3
[0069] The preparation method of the unfired and unsteamed brick product is basically the same as the preparation method of Example 1, except that the amount of water glass added in step S2 is 2.5 kg.
[0070] Comparative Example 4
[0071] The preparation method of the unfired and unsteamed brick product is basically the same as the preparation method of Example 1, except that the amount of water glass added in step S2 is 15 kg.
[0072] Comparative Example 5
[0073] The preparation method of the unfired and unsteamed brick product is basically the same as the preparation method of Example 1, except that the amount of water glass added in step S2 is 20 kg.
[0074] Comparative Example 6
[0075] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the retarder A used in step S3 is replaced by a five-membered copolymer of methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C with a number average molecular weight of 38,000, and the added weight remains unchanged.
[0076] Comparative Example 7
[0077] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the retarder A used in step S3 is replaced by a five-membered copolymer of methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C with a number average molecular weight of 46,000, and the added weight remains unchanged.
[0078] Comparative Example 8
[0079] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the retarder A used in step S3 is replaced by titanium gypsum, the content of CaSO4·2H2O in the titanium gypsum is 84.7%, and the added weight remains unchanged.
[0080] Comparative Example 9
[0081] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the retarder A used in step S3 is replaced by a pentacrylic acid of methyl allyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C, the number average molecular weight of which is 41,000, and the added weight remains unchanged.
[0082] Comparative Example 10
[0083] 180 g of methylthioallyl alcohol polyoxyethylene ether (number average molecular weight is 3800), 20 g of acrylic acid, 20 g of butyl acrylate, 1.2 g of mercaptopropionic acid, and 0.5 g of vitamin C were mixed at room temperature to obtain retarder D.
[0084] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the retarder A used in step S3 is replaced by retarder D, and the added weight remains unchanged.
[0085] Comparative Example 11
[0086] The preparation method of the unfired and steamed brick product is basically the same as the preparation method of Example 1, except that the retarder A used in step S3 is replaced by methylthioallyl alcohol polyoxyethylene ether (number average molecular weight is 3800), and the added weight remains unchanged.
[0087] The unburned and steamed bricks prepared in the embodiments of the present invention and the comparative examples were subjected to strength test according to the Standard for Test Methods for Basic Properties of Building Mortar (JGJ / T70-2009). The compression test was conducted using a DYE-300N pressure testing machine, with uniform loading at a rate of 2400N / s±200N / s. The unburned and steamed bricks prepared in the embodiments of the present invention and the comparative examples were placed in a dark place for 28 days to observe the alkali reversion phenomenon. The test results are shown in Tables 1, 2, and 3:
[0088] Table 1
[0089]
[0090] It can be seen from Table 1 that the strength of bricks without adding nano-silica powder is relatively low. Adding nano-silica powder has excellent performance in improving the strength of bricks. The amount of nano-silica powder added that matches the compressive strength can be selected according to construction requirements.
[0091] Table 2
[0092]
[0093] It can be seen from Table 2 that reducing the amount of water glass added will slightly reduce the compressive strength of the brick body, but increasing the amount of water glass added does not significantly improve the strength of the brick body and will cause obvious alkali reversion. Therefore, Example 1 is the best implementation scheme.
[0094] Table 3
[0095]
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A high-content solid waste-based zero-cement addition non-fired and non-steamed brick, characterized in that: The invention comprises the following raw materials in parts by weight: 65-75 parts fly ash, 5-10 parts of calcium carbide slag, 10-15 parts of gypsum, 10-20 parts of nano-silicon powder, 10-20 parts of mineral powder, 5-10 parts of water glass, Retarder 0.1-0.2 parts, 50-55 parts of water; The retarder is a five-element copolymer with methylthioallyl alcohol polyoxyethylene ether as a functional monomer; The five-element copolymer is prepared by polymerizing methylthioallyl alcohol polyoxyethylene ether, acrylic acid, butyl acrylate, mercaptopropionic acid, and vitamin C; The number average molecular weight of the five-membered copolymer is 40,000-44,000; The number average molecular weight of the methylthioallyl alcohol polyoxyethylene ether is 3800; The size of the nano silicon powder is 20-200 nm.
2. The high-content solid waste-based zero-cement addition non-fired and non-steamed brick according to claim 1, characterized in that: The preparation method of the five-membered copolymer is as follows: 180 parts by weight of methylthioallyl alcohol polyoxyethylene ether are added to 1000 parts by weight of deionized water, heated to dissolve, 2.5 parts by weight of hydrogen peroxide are added, and then 50 parts by weight of a deionized water solution containing 20 parts by weight of acrylic acid, 20 parts by weight of butyl acrylate, 1.2 parts by weight of mercaptopropionic acid and 0.5 parts by weight of vitamin C are dripped at a uniform rate, and sodium bicarbonate solution is added to adjust the pH to 6.5, and the reaction temperature is controlled to maintain at 80°C for 8 hours to obtain a methylthioallyl alcohol polyoxyethylene ether-acrylic acid-butyl acrylate-mercaptopropionic acid-vitamin C five-membered copolymer.
3. The method for preparing a high-content solid waste-based zero-cement addition non-fired and non-steamed brick according to claim 1, characterized in that: The following steps are involved: S1: fly ash, carbide slag, gypsum and mineral powder are mixed in proportion to obtain a premixed dry powder; S2: Mix and stir nano-silica powder, water glass and half of water in proportion to obtain an excitation enhancer; S3: adding the excitation enhancer and the retarder to the premixed dry powder, and adding the remaining half of the water, stirring to obtain a gelling material; S4: putting the mixed cementitious material into a mold and vibrating it to obtain a green brick; S5: placing the green bricks at a temperature of 20-30°C and a humidity of 95-99% for curing for 14-28 days to obtain the unfired and unsteamed bricks.
Citation Information
Patent Citations
Multi-solid-waste baking-free steaming-free water permeable brick with double-layer structure and preparation method thereof
CN111892364A
Steaming-free and baking-free brick and preparation method thereof
CN112408935A
Powder solid waste granulation baking-free brick and preparation method thereof
CN113307576A
All-solid-waste baking-free brick prepared from multi-industry solid wastes and preparation method thereof
CN113929371A
Method for synergistically preparing baking-free steaming-free cured bricks from squeezed fine silt and lithium slag obtained after lepidolite beneficiation based on carbon curing
CN114031341A